2016
DOI: 10.1111/hepr.12834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium glucose cotransporter 2 inhibitor on liver function tests in Japanese patients with non‐alcoholic fatty liver disease and type 2 diabetes mellitus

Abstract: Sodium glucose cotransporter 2 inhibitor can be a novel promising agent for the treatment for NAFLD patients with T2DM. Prospective randomized controlled trials are warranted to confirm this efficacy of SGLT2I on NAFLD with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 17 publications
0
82
1
2
Order By: Relevance
“…In Japanese patients with T2DM refractory to dietary intervention with or without antidiabetic drugs, treatment with ipragliflozin (50–100 mg/day) for 12 weeks reduced transaminase activities as well as body weight and body fat . We also recently found that treatment with SGLT2 inhibitors for T2DM patients with biopsy‐proven NAFLD significantly reduced serum transaminase activities as well as body weight and body fat . Thus, we undertook subanalyses in phase II or III trials with canagliflozin from Japan to examine whether canagliflozin can decrease serum transaminase activities in Japanese patients with T2DM.…”
Section: Novel Antidiabetic Drugsmentioning
confidence: 99%
“…In Japanese patients with T2DM refractory to dietary intervention with or without antidiabetic drugs, treatment with ipragliflozin (50–100 mg/day) for 12 weeks reduced transaminase activities as well as body weight and body fat . We also recently found that treatment with SGLT2 inhibitors for T2DM patients with biopsy‐proven NAFLD significantly reduced serum transaminase activities as well as body weight and body fat . Thus, we undertook subanalyses in phase II or III trials with canagliflozin from Japan to examine whether canagliflozin can decrease serum transaminase activities in Japanese patients with T2DM.…”
Section: Novel Antidiabetic Drugsmentioning
confidence: 99%
“…Several SGLT2 inhibitors have shown benefit in murine models of NAFLD, improving steatosis, inflammation, and fibrosis, and studies in humans with T2DM have demonstrated improved ALT and weight loss in patients with type 2 diabetes with ipragliflozin and canagliflozin, as well as reducing fatty liver index score (from 70.1±19.4 to 60.3±25.5, P =.0009) with ipragliflozin . There are no reported human studies assessing changes in liver histology in NAFLD with SGLT2 inhibitors, although one study did demonstrate weight‐independent improvements in serum ALT with ipragliflozin …”
Section: Medications Currently Used In Patients With Nash To Treat Comentioning
confidence: 99%
“…All included studies noted a significant improvement in AST and ALT. Some studies also noted that this improvement exceeded or matched that of other diabetes medications such as metformin, pioglitazone, or sitagliptin . Similarly, 5 studies have evaluated the impact of SGLT‐2 inhibitors on hepatic fat and noted significant improvement .…”
Section: Treatment Optionsmentioning
confidence: 97%